Probability of the level number in a given energy interval - Zharekeshev, I.Kh. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
The statistics of the energy spectra for random electron systems are investigated near the metal-insulator transition. The fluctuations of the number of one-electron states in a finite energy interval are considered. The total probability of the level number is shown to be scale-invariant. The results are obtained at the critical point with and without time-reversal symmetry. The existence of the critical statistics is a prominent signature of the localization transition.
Keywords: metal-insulator transition; level number; critical statistics; energy spectra; transition